Recent findings in production and health benefits of prebiotics; a review of literatures - Abdorrasoul Malekpour; Mehdi Forouzesh; Saeid Gholamzadeh; Younes Ghasemi; Mohammad Moaddeli (Shiraz University of Medical Sciences, 2018)
Prebiotics are known as fermented ingredient with specific health benefits. The two main fermentative substrates of dietary origin are non-digestible carbohydrates and proteins which escape digestion in the small intestine. Beside traditional protocols for production of prebiotics, there are some commercial advanced methods for mass production of prebiotics with acceptable health effects. On the other hand, different types of nondigestible oligosaccharides (NDO) are used in the food and drug industries as functional foods and nutraceuticals due to their prebiotic effects and also immunomodulation effects (ex. SCFA modulate chemokine expression in intestinal epithelial cells). Prebiotics with novel and wide variety of health benefits deal with a bright future for improving society health.